Design and characterization of receive-only surface coil arrays at 3T with integrated solid high permittivity materials - Ruytenberg, Thomas; O'Reilly, Thomas P.; Webb, Andrew G. (Journal of magnetic resonance (1997), 2020)
[Display omitted] •Integrating high permittivity material (HPM) into coils increases SNR.•Using HPM with relative permittivity of 660, up to +52% SNR is obtained in the neck.•HPM with even higher permittivity potentially offers more benefits. A receive-only surface coil array for 3 Tesla integrating a high-permittivity material (HPM) with a relative permittivity of 660 was designed and constructed and subsequently its performance was evaluated and compared in terms of transmit field efficiency and specific absorption ratio (SAR) during transmission, and signal-to-noise ratio during reception, with a conventional identically-sized surface coil array. Finite-difference time-domain simulations, bench measurements and in-vivo neck imaging on three healthy volunteers were performed using a three-element surface coil array with integrated HPMs placed around the larynx. Simulation results show an increase in local transmit efficiency of the body coil of ~10-15% arising from the presence of the HPM. The receiver efficiency also increased by approximately 15% close to the surface. Phantom experiments confirmed these results. In-vivo scans using identical transmit power resulted in SNR gains throughout the laryngeal area when compared with the conventional surface coil array. In particular specifically around the carotid arteries an average SNR gain of 52% was measured averaged over the three subjects, while in the spine an average of 20% SNR gain was obtained.